2014
DOI: 10.2807/1560-7917.es2014.19.29.20857
|View full text |Cite
|
Sign up to set email alerts
|

Case of Legionnaires’ disease in a neonate following a home birth in a heated birthing pool, England, June 2014

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…; Phin et al . ). Patients can thus be linked to an environmental source by qPCR alone (Mentasti et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Phin et al . ). Patients can thus be linked to an environmental source by qPCR alone (Mentasti et al .…”
Section: Discussionmentioning
confidence: 97%
“…Samples were analysed by the PHE Food, Water and Environmental Microbiology (FW&E) laboratories using a method based on ISO 11 731 and by a recently validated (ISO TS 12 869:2012) quantitative polymerase chain reaction (qPCR) method for Legionella species, L. pneumophila and L. pneumophila sg1 [11]. Elizabethkingia meningoseptica, an opportunistic pathogen that can cause infections in infants [14] was identified by culture and matrix-assisted laser desorption ionization-time of flight (MALDI-ToF) as the major contaminant [9]. Quantitative PCR testing revealed four samples to be L. pneumophila sg1 positive.…”
Section: Environmental Investigationmentioning
confidence: 99%
“…Series and single cases of ECLS for severe Legionella pneumonia in adult patients have been reported, 6-8 but, to our knowledge, only 1 case of ECMO support for neonatal Legionella infection is reported in the literature with no mention of outcome. 16 Query of the Extracorporeal Life Support Organization registry (1990-2014) identified 2 neonatal cases (9 and 17 days of life) and 2 infants with Legionella pneumonia supported with venovenous or venoarterial ECMO with no survivors. In the most recent retrospective study of 12 adult patients with Legionella pneumonia treated with VV-ECMO, 75% of patients were successfully weaned off ECLS, with 67% survival to discharge, 6 compared with 25% survival in a previous study of 8 confirmed cases.…”
Section: Figurementioning
confidence: 99%